The Parameters Discharge, Salinity and Dissolved loads of Tigris River from Mosul to Baghdad, Iraq - Oleiwi, Alyaa Shakir; Al-Dabbas, Moutaz (Iraqi Journal of Science, 2024)
The Tigris River is the most significant source of water in Iraq. Iraq has been through periods of drought due to climate change and numerous water infrastructure projects that were carried out in the Tigris Basin of Turkey. Four sites have been selected for environmental pollution evaluation, the impact of climate change on the hydrochemistry of the Tigris River, and an estimate of the relationship between dissolved loadings and discharges (m3/s). Data includes Tigris River discharge and hydrochemical analysis: major ions such as (Ca, Mg, Na, K, Cl, SO4, and HCO3), minor ions (NO3 and PO4), trace elements, and biological parameters (BOD5, C.O.D., E-Coli Bacteria, Fecal Coliform Bacteria) as indicators of contamination allowing the identification of sources of pollution. The Tigris River is within the allowable drinking limits, except in the Tharthar-Tigris Canal, and the most ions that have an impact on the Tigris River’s water quality are total dissolved solids, E. coli Bacteria, Fecal Coliform Bacteria, BOD5, and C.O.D. Total ionic salinity (meq/l) was less than 20 in the Mosul and Sammara sites, 20 in the Tharthar-Tigris Canal, and between 20 and 40 in the Baghdad site. By applying for the SPSS program, two factors were identified. The first factor represents 84.03 % indicates (natural factor) represented by the weathering of rocky components of the river. The second factor represented 11.33% (Anthropogenic factor), represented by agricultural wastewater, waste and sewage water thrown directly into the river.